Pengaruh Transaksi Non-Tunai Terhadap Tingkat Inflasi, Suku Bunga, dan Uang Beredar di Indonesia - Maulana, Alhakki (Educationist: Journal of Educational and Cultural Studies, 2023)
Non-cash transactions had emerged as new way of conducting financial transactions in recent years, brings about substitution and efficiency effects that can influence the money supply, interest rates, and price levels. This research aims to analyze the impact of non-cash transaction usage on the economy through money supply, interest rates, and inflation. Vector Error Correction Model (VECM) is used in this study to examine the two-way effect of non-cash transactions on money supply, interest rates, and price levels from 2014 until 2022, revealing short and long-term connections. Impulse Response Functions (IRF) and Forecast Error Variance Decomposition (FEVD) help illustrate how one variable's disturbances affect other.